2013
DOI: 10.7860/jcdr/2013/6441.3215
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Pattern and Familial Effects of Substance Use Among the Male College Students –A North Indian Study

Abstract: Prevalence of substance use was seen in 52.7% students belonging to age group 19 to 21 years. More prevalence of substance use was found among law students (76.2%) followed by the students from Art stream (62.5%). Among the users alcohol was most commonly used (53.5%), followed by smokers (27.3%), tobacco chewers (8.2%), cannabis (6.8%).49% of the users were using substances on daily basis, followed by 23% who using weekly.29.3% of users had father using any substance. Relief from psychological stress (66.0%) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 7 publications
5
47
0
Order By: Relevance
“…On the other hand, Sorsdahl et al concluded that there are differences in ASA in terms of sex and males are more inclined to engage in substance abuse than females ( 35 ). Moreover, Gupta et al suggested that tendency to substance abuse is more prevalent among male college students than female ones ( 3 ). It may be concluded that low SES, especially among males, is the main contributor of tendency toward substance abuse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Sorsdahl et al concluded that there are differences in ASA in terms of sex and males are more inclined to engage in substance abuse than females ( 35 ). Moreover, Gupta et al suggested that tendency to substance abuse is more prevalent among male college students than female ones ( 3 ). It may be concluded that low SES, especially among males, is the main contributor of tendency toward substance abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the longstanding history of substance related disorders in the world, it has become a serious global problem in recent times and is affected by psychosocial, economic, individual, familial, and political factors ( 1 , 2 ). Substance abuse applies to the using of any psychoactive substances, licit, illicit, or medically prescribed drugs ( 3 ). Recent evidences show that prevalence of alcohol consumption and substance abuse, especially new drugs such as ecstasy, is increasing among Iranian university students ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a few studies have been conducted in Asian countries, and information on types of illicit drugs included in the studies were limited. In a study in India, 7% of the students reported cannabis use [16]. In the Middle East, lifetime prevalence of illicit drug use was 14% in Kuwait [15], and the prevalence of current use was 8% in Iran [17].…”
Section: Introductionmentioning
confidence: 99%
“…In most of the existing studies, illicit drug use is combined with other substances in the analyses [16, 18], making the interpretation of the findings difficult. Therefore, this study was conducted to explore the prevalence of and factors associated with illicit drug use among university students in Cambodia, Indonesia, Laos, Malaysia, Myanmar, the Philippines, Singapore, Thailand and Vietnam.…”
Section: Introductionmentioning
confidence: 99%